Myocardial contusion: emergency investigation and diagnosis. Issue 1 (1st January 2002) - Kaye, P; O'Sullivan, ĺ
Abstract : Cardiac contusion is an infrequent but occasionally serious complication of deceleration injury. According to ATLS teaching, the true diagnosis of contusion can only be established by direct inspection of the myocardium. The clinically important sequelae of myocardial contusion are hypotension and arrhythmia. Despite recent advances in investigative techniques, myocardial trauma remains an important diagnostic and management challenge. This paper presents an evidence-based review of the topic.